Sound sample detection and numerosity estimation using auditory display - Gamper, Hannes; Dicke, Christina; Billinghurst, Mark; Puolamäki, Kai (ACM Transactions on Applied Perception, 2013)
This article investigates the effect of various design parameters of auditory information display on user performance in two basic information retrieval tasks. We conducted a user test with 22 participants in which sets of sound samples were presented. In the first task, the test participants were asked to detect a given sample among a set of samples. In the second task, the test participants were asked to estimate the relative number of instances of a given sample in two sets of samples. We found that the stimulus onset asynchrony (SOA) of the sound samples had a significant effect on user performance in both tasks. For the sample detection task, the average error rate was about 10% with an SOA of 100 ms. For the numerosity estimation task, an SOA of at least 200 ms was necessary to yield average error rates lower than 30%. Other parameters, including the samples' sound type (synthesized speech or earcons) and spatial quality (multichannel loudspeaker or diotic headphone playback), had no substantial effect on user performance. These results suggest that diotic, or indeed monophonic, playback with appropriately chosen SOA may be sufficient in practical applications for users to perform the given information retrieval tasks, if information about the sample location is not relevant. If location information was provided through spatial playback of the samples, test subjects were able to simultaneously detect and localize a sample with reasonable accuracy.
http://doi.acm.org/10.1145/2422105.2422109